UPAYA PENANAMAN NILAI-NILAI PENDIDIKAN KARAKTER PADA SISWA MELALUI KEGIATAN KEAGAMAAN DI MI HIDAYATUL MUBTADI’IN TASIKMADU MALANG - Saleh Y. Kampoh; Azhar Haq; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2021)
Thus this research tries to pour out some ideas about how to instill the values of character education through religious activities. The results showed that (1). the efforts of the Head of Madrasah and Madrasah Ibtidaiyah Teachers have reached very high abilities, In terms of the process of creating students to achieve good character values, it is very optimal and has changes that are starting to be seen from students, educators, parents and the surrounding community, (2) the obstacles faced in the process of inculcating the values of character education through religious activities at Madrasah Ibtidaiyah Hidayatul Mubtadiin Tasikmadu, namely the negligence of students to bring juz 'ammah or Al-Qur'an, students who are difficult to condition, and parents' lack of awareness of the importance of assistance in child development. As for the supporting factors, namely Madrasah Ibtidaiyah Hidayatul Mubtadiin Tasikmadu Malang City has several facilities that are sufficient to support the planned process effort, The Madrasah is located right in the heart of the Hidayatul Mubtadiin Islamic Boarding School, the residents of the Madrasah are very helpful in supervising students, (3) based on the efforts to instill values and character that are practiced at Madrasah Ibtidaiyah Hidayatul Mubtadiin Tasikmadu Malang City, it forms a good character for students, religious activities in Madrasah Ibtidaiyah Hidayatul Mutbadiin Tasikmadu Malang City which are formed from these efforts are. 5S (Smile, Greetings, Greetings, Polite, Polite), pray together, pray dhuha and dhuhur prayer in congregation, muraja'ah memorization, and Hajj rituals. The character values instilled through religious activities are religious values, discipline, and responsibility.